Genoese Entrepreneurship and the Asiento Slave Trade, 1650-1700 - Garcia-Monton, Alejandro (Early Modern Iberian History in Global Contexts: Connexions, 2022)
1650-1700, Asiento, Entrepreneurship, Genoese, Slave, Trade